Form four students' attitude towards statistics - Siaw, Pei Ching (Universiti Malaysia Sarawak (UNIMAS), 2009)
This research is carried out to investigate Form Four students'attitude towards Statistics in two secondary school in Sibu district. The aspects that the study aimed to find out whether Form Four students possess positive or negative attitude towards the learning of Statistics. Besides that, this study also aimed to explore the relationship between Form Four students' attitude towards Statistics based on six subscales in terms of gender and learning styles. One hundred students from two schools in Sibu were used as a sample for this study. The "Survey of Attitudes Toward Statistics-36" (SATS-36) were used as the measure of attitude towards Statistics. The research design used was the survey questionnaire. Pearson-product moment correlations were used to measure the relationship between the subscales of attitude toward statistics. The Independent t-test was used to determine the difference in attitude towards the learning of Statistics based on six subscales between male students and female students. The ANOVA test was used to determine the difference in attitude towards Statistics based on six subscales among visual, auditory and kinaesthetic learners. The results showed that there were significant differences in attitude towards the learning of Statistics based on six subscales among male and female students. In addition, there were significant differences in attitude towards the learning of Statistics based on six subscales among visual, auditory and kinaesthetic learners. The results also indicated that Form Four students exhibited negative attitude towards Statistics.